2022
DOI: 10.3389/fresc.2022.1023740
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorders among secondary school teachers in Douala, Cameroon: The effect of the practice of physical activities

Abstract: IntroductionMusculoskeletal disorders (MSDs) represent an important threat to public health in both developed and developing countries, and are present in many occupational sectors including education. Regular practice of physical activity (PA) is known elicit preventive effects on the occurrence of MSDs.ObjectiveThis study aimed at determining the prevalence of MSDs and the preventive impact of PA on their occurrence among secondary school teachers.Participants and MethodsA cross-sectional study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The study's findings shed light on the significant prevalence of MSD among teachers and other school staff and would also help educational institutions and policymakers take measures to promote safe and healthy working conditions for teachers to prevent the development of MSDs and improve their work performance. The gender distribution displayed a majority of females (65.1%), highlighting the gender composition in the teaching profession and in teachers with MSD reported by other studies [ 1 ]. The prevalence of MSD, as indicated by the self-reported symptoms, such as pain and discomfort, varied across body regions.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The study's findings shed light on the significant prevalence of MSD among teachers and other school staff and would also help educational institutions and policymakers take measures to promote safe and healthy working conditions for teachers to prevent the development of MSDs and improve their work performance. The gender distribution displayed a majority of females (65.1%), highlighting the gender composition in the teaching profession and in teachers with MSD reported by other studies [ 1 ]. The prevalence of MSD, as indicated by the self-reported symptoms, such as pain and discomfort, varied across body regions.…”
Section: Discussionsupporting
confidence: 60%
“…The term "musculoskeletal disorders" (MSDs) refers to a group of periarticular conditions that affect the musculoskeletal system and primarily cause functional discomfort and everyday pain [ 1 , 2 ]. Musculoskeletal disorders (MSDs) are more prevalent among schoolteachers, who are required to spend long periods of time standing, sitting, and engaging in repetitive tasks, such as grading papers or typing on a computer [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown a clear significant association between physical activity habits and the prevalence of MSDs. Additionally, the lack of exercise has been found to increase the occurrence of these problems [ 20 , 21 ]. This could be attributed to the impact that physical activity has on the status of muscles, as it increases their mass and functionality.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Chile in the year 2021 concluded that there indeed was a strong association between teachers' reporting a lower quality of life and having musculoskeletal pains or disorders acquired through teaching or at the workplace. Two additional studies conducted in 2022 found that female teachers were more prone to this pain-induced reduction in the quality of life (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%